Particularizing the Universal: Dave Eggers Writes Human Rights. Issue 1 (2nd January 2016) - Bex, Sean
Abstract : This article examines the ways in which two literary texts by the American author Dave Eggers, his novel You Shall Know Our Velocity (2002) and his short story "Up the Mountain Coming Down Slowly, " interrogate the abstract humanism that underlies universalist rights and explore the reasons for their ineptitude at effecting their promise of universalism when faced with the particularity of individual cultures. Thematically, Eggers's stories test the limits of promoting rights on the basis of an innate shared humanity by exposing how such a basis easily slides into other universalist practices such as those of neocolonialism and neoimperialism. At the character level, these narratives consider the possibilities for meaningful cross-cultural relationships within the context of these discourses, revealing the ease with which they in turn can slip into hierarchical relations that reaffirm existing divisions. In doing so, they also engage and challenge the conclusions of cosmopolitan thinkers such as Kwame Anthony Appiah or Jürgen Habermas who have influentially proposed cross-cultural dialogues as a means of overcoming the tension between universalism and particularity. Interestingly, then, even as interdisciplinary research on literature and human rights has begun to etch out the coalescence of the two, Eggers provides an important example of how literary texts can also critique human rights discourses and can explore questions pertaining to their global reach.